Trends in colorectal cancer by subsite, age, and gender over a 15-year period in Adana, Turkey: 1993-2008 - Gülşah SEYDAOĞLU; Birol ÖZER; Nilgün ARPACI; Cem Kaan PARSAK; İsmail Cem ERAY (Turkish Journal of Gastroenterology, 2019)
-